Análisis teórico de la aplicación del impuesto diferido bajo las normas internacionales de información financiera y la aplicación bajo la norma Nacional Colombiana. (2020)
The implementation of the International Financial Reporting Framework as the accounting regulatory framework and the tax regulatory frameworks in Colombia, mark variables that can change the procedure of recognition, measurement and calculation of deferred tax in the accounting of any company, which is why we want to establish a degree of theoretical uniformity that establishes the dimensions in which the different aspects that mark the main divergences are framed when putting into practice the normative frameworks. Taking into account that this aspect may affect the financial and tax accounting of a company, it is necessary to evaluate them so that the importance of accounting - financial and tax planning that benefits the company's decisions can be established, in such a way that it reflect the reality of the company, helping to mitigate the impact of the temporary differences that these mean.